Model Make-A-Match Berbasis Kearifan Lokal Temanggung untuk Meningkatkan Hasil Belajar Matematika - Hamidulloh Ibda; Erlina Novita Sari (Balai Diklat Keagamaan Semarang, 2024)
The lack of innovation in learning impacts the low learning outcomes for class I Mathematics at MI Al-Ma'arif Kupen, Temanggung Regency. The research aims to reveal the implementation of the make-a-match model through picture cards based on local Temanggung wisdom in improving Mathematics learning outcomes. This research method is collaborative Class Action Research with the Kemmis & Taggart type consisting of 2 stages of the PTK cycle. Data collection techniques are observation, in-depth interviews, tests, document studies, and source triangulation, namely techniques used to increase the validity and reliability of research findings by comparing and verifying data obtained from various sources. The research subjects were 30 class I students at MI Al-Ma'arif Kupen, Temanggung Regency. The research results show that students' mathematics learning outcomes in the cognitive aspect using the make-a-match learning model through picture cards based on local wisdom in Temanggung increased according to the pretest and posttest results, which improved quite well. Before the action, classical learning results were only 13.3% with an average class score of only 40.3 points; in cycle I, there was an increase of 75.3 with classical learning completeness of 80%; and in cycle II, there was an increase in classical learning completeness in numbers. 96.6%, with an average score of 96. Further research needs to be carried out to examine in more depth the make-a-match model in Mathematics subjects according to current developments.